Analisis Sengketa Tanah Akibat Sertifikat Ganda Dalam Perspektif Hukum Perdata - Nurhayati, Siti; Suardi, Suardi (Neolectura, 2026)
The purpose of this research is to find out what are the main factors that cause double certificates in land dispute cases and to find out the legal consequences of double certificates and know the settlement mechanism in the perspective of civil law. This research uses a normative juridical approach method, which is a legal research method that relies on the study of applicable legal norms supported by a case approach to see how the court applies legal norms in practice. From this research the author draws the following conclusions: First, that broadly speaking the factors causing the existence of multiple certificates can be categorized into 3 aspects, namely the first technical aspect, which relates to the mapping system and land documentation. Second, administrative aspects such as errors in collecting and processing physical and juridical data by the BPN. Third, social factors/aspects, which are related to low public understanding of land rights and land registration procedures. Second, disputes due to multiple certificates can be resolved through litigation and non-litigation channels. Litigation is conducted through a lawsuit in court, while non-litigation can be in the form of mediation, arbitration, or settlement through the Land Office.